Strategic Analysis of Mediterranean Island Destinations: The Case of Corfu - KONTOGEORGIS, Georgios; LIVAS, Christos; KARALI, Nansy (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022DO - 10.14505/jemt.v13.6(62).01, 2022)
Apart from having a long tourism tradition, due to its geographic location and predominantly pleasant climatic conditions, Greece has primarily relied on tourism to recover from its prolonged economic hardships. Consequently, the present study aims at conducting a strategic analysis of Corfu, an important tourist destination located in the Ionian Sea, with the purpose of suggesting targeted interventions regarding the island’s tourism product and providing directions for sustainable tourism development. Secondary data analysis and results from a survey of 334 tourists indicated several strengths, weaknesses, opportunities, and threats concerning Corfu’s tourism sector. This information reveals a number of ways to improve Corfu’s overall tourism product and develop a sustainable strategy for the Corfiot tourism industry. In view of rising environmental and socioeconomic challenges, a comprehensive tourism strategy ought to simultaneously enhance Corfu’s competitive position, improve residents’ welfare and safeguard the island’s scarce natural resources.